Tax Haven: Latin America and its Struggle 2018 – 2023 - Giudice Baca, Victor (2024)
Tax havens have considerably reduced tax revenues and Latin American countries are the most affected than developed countries. The main allied institution of Latin American countries to counter tax evasion, tax avoidance and illicit cash flows is the OECD and since 2018 with its meeting in Punta del Este it has established concrete measures and objectives that have been implemented and developed. Latin American countries have to commit to the development of fiscal transparency and information exchange mechanisms to counteract tax havens.